2022
DOI: 10.1590/fst.64021
|View full text |Cite
|
Sign up to set email alerts
|

Probiotic fermented beverages processed with water-soluble rice extract and added with curdlan oligosaccharides and oligofructose: physicochemical characteristics, rheological parameters, and storage stability

Abstract: The effect of oligofructose and/or curdlan oligosaccharides (CO) addition on the characteristics of probiotic fermented beverages processed with water-soluble rice extract (WSRE) was evaluated. The products were assessed for the physicochemical characteristics, rheological parameters, and probiotic survival (L. casei) during storage (28 days, 7 °C). Probiotic counts higher than 10 8 CFU mL -1 and 10 6 CFU mL -1 were observed during storage and after simulated gastrointestinal conditions (SGIC). Oligofructose a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Several studies have shown that both rice and coconut water are optimal materials for the growth of probiotics. 43 , 44 Therefore, this study highlights that the physicochemical properties obtained from formulations based on coconut water and rice flour can be proposed as a symbiotic beverage (a mixture comprising live microorganisms and substrates used by these for their growth), which confers a health benefit. 43 …”
Section: Resultsmentioning
confidence: 95%
See 3 more Smart Citations
“…Several studies have shown that both rice and coconut water are optimal materials for the growth of probiotics. 43 , 44 Therefore, this study highlights that the physicochemical properties obtained from formulations based on coconut water and rice flour can be proposed as a symbiotic beverage (a mixture comprising live microorganisms and substrates used by these for their growth), which confers a health benefit. 43 …”
Section: Resultsmentioning
confidence: 95%
“… 43 , 44 Therefore, this study highlights that the physicochemical properties obtained from formulations based on coconut water and rice flour can be proposed as a symbiotic beverage (a mixture comprising live microorganisms and substrates used by these for their growth), which confers a health benefit. 43 …”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations